NUTRI-EPIGENETIC MODULATION IN WOMEN: THE POTENTIAL OF CAATINGA’S NEGLECTED SPECIES IN MODULATING FOOD INSECURITY-RELATED EPIGENETIC MARKS - Roberto Ramos, Paulo; Almeida Ferreira, Rodrigo; Dourado Carvalho, Luzineide; de Almeida Araújo, Cleyton; Cordeiro Pereira, Sidclay; Frensch, Gustavo; Silva Carvalho, Rubens; de Deus Cysneiros Cavalcanti, Airton; Mara Marinho da Silva, Lícia; Gomes de Lima, Carlos; Santana de Jesus, Mariana; Henrique Martins Cavalcante, Edmo; et al. (Revista Gênero e Interdisciplinaridade, 2026)
Food insecurity has emerged not only as a socioeconomic issue but as a molecular determinant capable of shaping epigenetic patterns and long-term health outcomes across generations. This study aimed to analyze how amino acids and bioactive metabolites from neglected and underutilized species (NUS) of the Caatinga may contribute to the modulation of DNA methylation processes and the mitigation of transgenerational epigenetic alterations in women exposed to nutritional vulnerability. An integrative review was conducted, based on an initial retrieval of 288 studies across major scientific databases, followed by systematic screening and selection, resulting in a final analytical corpus of 34 references. The synthesis revealed that Caatinga NUS, particularly drought-adapted species, exhibit biochemical profiles rich in amino acids, antioxidants, and methyl donor-related compounds. These elements are directly associated with one-carbon metabolism and the regulation of epigenetic enzymes such as DNA methyltransferases and histone deacetylases. The discussion highlights a conceptual shift in which plant stress metabolites are interpreted as potential substrates for human epigenetic resilience. In this context, the study proposes the concepts of Epigenetic Sovereignty and Nutritional Bioremediation as integrative frameworks linking biodiversity, nutrition, and molecular health. The findings suggest that incorporating locally adapted species into nutritional strategies may represent a promising pathway for addressing health inequities and improving epigenetic outcomes in food-insecure populations.